THE OBJECTIVE CONDITIONS ON SOCIAL ASPECTS OF MARABAHAN BARU VILLAGE AS A BUFFER VILLAGE OF CURIAK ISLAND - Abbas, Ersis Warmansyah; Koswara, Deden; Fahmanadie, Daddy; Ilhami, M. Ridha; Mursalin, Arisandy; Husna, Nur; Julia, Siti (International Conference On Social Science Education, 2024)
This research project aims to examine the objective conditions of Marabahan Baru village, which serves as a buffer zone for Curiak Island. In particular, the research will focus on the social aspects of the local community. This research employs a qualitative approach, utilising field observations, in-depth interviews and secondary data analysis. The findings revealed that Marabahan Baru village, serving as a buffer zone for Curiak Island, confronts a multitude of social challenges, including relatively low educational attainment and restricted access to healthcare services. This research concludes that a unified approach is essential to enhance the well-being of the community in the buffer zone of Curiak Island, one such strategy being a community empowerment programme.